KEMAMPUAN KONSEP BILANGAN DAN BERCERITA PADA ANAK KELOMPOK A MELALUI PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI TK BAITUL ILMI PANJANG JIWO SURABAYA - Susi Maulida (Universitas Islam Lamongan, 2019)
This study aims to determine the effect of Contextual Teaching and Learning (CTL) learning model in the ability of storytelling and cognitive.The used approach research is quantitative research with experimental research model, Where researchers provide treatment in the form of learning by using CTL And make observations in the learning activities of children in the classroom and make measurements before and after giving treatment. The research was conducted using the experimental model design or Quasi Experimental design, which this design has a control group but can not function fully to control the outside variables that affect the implementation of the experiment.Â This study used the Nonequivalent Control Group Design, which the experimental group and the control group were not randomly selected. Based on the results of the analysis it can be concluded there is a significant increase on the ability to tell stories using CTL approach of 9.18> 7.82. As for the concept of numbers there is also a significant increase of 18,0909> 13.2273.